2018
DOI: 10.1017/s1368980018000964
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver perceptions of a fruit and vegetable prescription programme for low-income paediatric patients

Abstract: A fruit and vegetable prescription programme involving a partnership between a farmers' market and paediatric clinic was perceived as effective in improving food security, food access and child consumption of fresh fruits and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(127 citation statements)
references
References 65 publications
2
117
1
7
Order By: Relevance
“…The current study, however, suggests that pediatric fruit and vegetable prescriptions have a significant impact on consumption of whole fruits, while having no influence on the consumption of fruit juice or vegetables. This finding supports previous qualitative work in Flint in which caregivers, who perceived the prescription program to have a positive influence on child consumption of fresh produce, described child preferences for fruits, particularly "new" fruits that farmers' market vendors encouraged children to taste for the first time while using their prescriptions [6]. These findings support accumulating evidence that child participation in food selection and preparation are effective in improving diet quality [67][68][69][70].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The current study, however, suggests that pediatric fruit and vegetable prescriptions have a significant impact on consumption of whole fruits, while having no influence on the consumption of fruit juice or vegetables. This finding supports previous qualitative work in Flint in which caregivers, who perceived the prescription program to have a positive influence on child consumption of fresh produce, described child preferences for fruits, particularly "new" fruits that farmers' market vendors encouraged children to taste for the first time while using their prescriptions [6]. These findings support accumulating evidence that child participation in food selection and preparation are effective in improving diet quality [67][68][69][70].…”
Section: Discussionsupporting
confidence: 87%
“…Although consumption of fruit has been associated with a reduced risk of obesity and chronic disease [1][2][3][4][5][6], better psychological well-being [1,[7][8][9], and improved gut health [1,10], intake fails to meet dietary recommendations among all but the youngest children in the US [11,12]. Considering the growing evidence of an association between greater fruit and vegetable consumption during childhood and reduced chronic diseases in adulthood [13][14][15][16], both short-and long-term implications of programs that successfully increase fruit intake among children are likely to be significant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has indicated that providers particularly appreciate that produce prescription programs allow them to provide resources that enable their clients to act on the lifestyle change advice they offer (10,21). Having an opportunity to provide such resources to clients may have facilitated counseling conversations about lifestyle behavior change and may have contributed to the significant increases in provider communication related to diet and fruit and vegetable consumption reported by participants.…”
Section: Discussionmentioning
confidence: 99%